Papers - Refining - Electrolytic Refining - Electrolytic Copper Refinery of Ontario Refining Company Limited at - Frederic Benard (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
The electrolytic copper refinery at Copper Cliff, Ont., is operated by the Ontario Refining Co., Ltd. The associated companies behind the enterprise are the International Nickel Co. of Canada, Ltd.; The American Metal Co.; The Consolidated Mining & Smelting Co. of Canada, Ltd.; and Ventures, Ltd. The plant was the outgrowth of the rapid development of copper resources in the nickel-copper ores of the Frood and other great mines in the Sudbury district, and of the desire to have all primary production units grouped together as closely as possible. The refinery is near the intersection of the Sault Ste. Marie to Sudbury highway and the Canadian Pacific Railway. It is about one mile south of The International Nickel Company's smelter at Copper Cliff. The standard-gage track systems of the refinery and of the smelter are connected by a standard-gage timber railroad trestle that crosses the railway and the highway by means of steel girder spans. The Canadian National Railway has access to the plant by means of this trestle and the nickel company's tracks, so that the refinery has connections with both the Canadian Pacific and the Canadian National railways, as well as a direct connection with The International Nickel Company's smelter, from which the bulk of the copper to be refined is hauled by the latter's electric locomotives. Buildings The refinery (Fig. 1) covers approximately 60 acres, enclosed by an unscalable chain-link fence. The main buildings have a content of 23,000,000 cu. ft., with a total roof area of approximately 600,000 sq. ft. and near them are the substation, cooling pond and main standard-gage track system (Fig. 2). A ladder track for car storage extends 1200 ft. south of the coal-pulverizer tracks and the scale house is on this spur. The intake and pumphouse for fresh water supply are at Kelly Lake, about 3000 ft. south of the plant. Owing to the severity of the winters, when temperatures of from 20" to 40' below zero are to be expected, the building of this refinery involved a number of problems in insulation, layout, ventilation, etc., which were